Global Strategy to Improve Agricultural and Rural Statistics - World Bank (Washington, DC, 2013)
Policy makers and development practitioners who are responsible for developing investment strategies to promote economic growth find many challenges in the changing face of agriculture in the twenty-first century. In addition to its productive role of providing food, clothing, fuel, and housing for a growing world population, agriculture assumes other roles, the importance of which has more recently been recognized. In addition to its essential role in food security, agricultural development is now seen as a vital and high-impact source of poverty reduction. It is also seen as a source of environmental problems and a contributor to global warming, water scarcity and pollution, and land degradation. At the same time its potential as a source of environmental services needs to be defined, monitored, and evaluated. Many of the issues facing the sector transcend national boundaries. The Global Strategy is the result of an extensive consultation process with national and international statistical organizations as well as with agriculture ministries and other governmental institutions represented in Food and Agricultural Organization of the United Nations (FAO) governing bodies. Considerable input came from the United Nations statistical commission friends of chair working group and the 2009 meetings of the International Statistical Institute in Maputo and Durban. Other collaboration involved the FAO Biannual conference and discussions at the regional commissions on agricultural statistics attended by national directors of agricultural statistics, the World Bank peer review process, and the development of a Wikipedia web page to collect inputs from the statistical community. The purpose of the global strategy is to provide a framework for national and international statistical systems that enables them to produce and to apply the basic data and information needed to guide decision making in the twenty-first century. This paper presents the overall strategy. It provides a ground-breaking effort to improve agricultural statistics that has implications for other sectors in the national statistical system. While it took many years for agriculture statistics to deteriorate to their current state, the implementation of the strategy provides a fresh start.